(untitled) (Journal of the College of Basic Education, 2022)
Measurements of physical and physical abilities help to know how similar in physical configuration, between groups of athletes who have achieved good results in certain sports, it helps to find out the differences in the physical configuration of the different activities, they also help in identifying the important measurements for various practitioners with high level and hence the importance of research to determine the requirements of events (and barriers) and ease of understanding of physical measurements and physical abilities to pick The talented and caring towards the first step in configuring the Olympic champion. In the absence of standards for gifted students was a problem, so I hope this albahathanan through their study results objective and accurate selection of players and their classification, by finding the standard levels of degrees through which the Sports trainer can choose the talented players. Research objectives: identify some physical measurements and physical abilities of the players speed and barriers. Find degrees and levels selected standard Universal Declaration. Research objectives: identify some physical measurements and physical abilities of the players speed and barriers. Find degrees and standard levels selected for players of ages (12-13). Albahathanan used descriptive survey style, and research society (6000) Cub in the first phase of tests and measurements, the researchers used statistical methods appropriate to find Spss. The results. Albahathanan concluded: it appears that the standard adopted by the grades they categorize the search community and converting the result to a meaningful quantitative researcher gave a clear picture of the level of the sample is categorized into six levels (very good, good, average, acceptable, weak, very weak). The researchers adopted ratios to determine levels of statistical level was very good 2.14% and the best achievements and measurements for the gifted is appropriated by the researchers to qualify for the second phase